Application and mechanism of graphene and polydopamine-modified graphene in anticorrosion coatings - Chen, Guangyan; Xiao, Zhuoting; Cao, Yuwei; Zhao, Wenjie; Xu, Yao; Xiao, Fei; He, Yongyong; Jin, Bao (Frontiers in Materials, 2025)
Owing to the great barrier properties, light weight and environmental friendliness, graphene-based anticorrosion coatings are considered to be promising candidates for next-generation anticorrosion materials. Recently, polydopamine has showed considerable research value and application prospects in the field of anticorrosion, and provided new opportunities for chemical modification of graphene for the enhancement of coating performance. However, the applications and mechanisms of polydopamine-modified graphene in anticorrosion coatings have not been systematically summarized. This review focuses on the application and mechanism of graphene and polydopamine-modified graphene in anticorrosion coatings. Firstly, the intrinsic barrier properties and applications of graphene in anticorrosion coatings are summarized, especially in self-healing anticorrosion coatings. Next, the properties and applications of polydopamine in the field of anticorrosion are reviewed and discussed. Moreover, the application and mechanism of polydopamine in graphene-based anticorrosion coatings are systematically reviewed, which mainly includes enhancing the intrinsic barrier properties, improving the dispersibility, modifying with functional materials, and introducing pH-responsive properties. Finally, the critical challenges and future prospects for the development of graphene-based anticorrosion coatings are discussed. This article aims to boost further development of graphene-based anticorrosion coatings to solve the anticorrosion bottleneck of equipment in harsh corrosive environments.